Effective Teaching Methodologies for Teaching Digital Controller Subject - Rama Rao, P. V. V.; Durga Prasad, G.; Venkata Ramana, N. (Journal of Engineering Education Transformations, 2025)
The digital controllers are gaining a significant part in an extensive variety of designing applications. Chip courses are at present educated by all building branches of all existing colleges on the planet. The traditional strategy for educating such courses to a great extent is in view of hypothesis and having lab course.Practice and application situated methodology in training is essential, and some do research on active learning and cooperative problem solving. It have shown that a student will learn faster and develop better communication skills, leadership qualities and team work ambiance through these methods. In this paper, another methodology is proposed for the educating of digital controller courses. This new approach empowers students to take in the down to earth utilization of digital controllers from a functional perspective.